2021
DOI: 10.3390/antiox10121868
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones Producing Acinetobacter bouvetii P1 Mitigates Chromate Stress in Sunflower by Provoking Host Antioxidant Response

Abstract: Different physical and chemical techniques are used for the decontamination of Cr+6 contaminated sites. The techniques are expensive, laborious, and time-consuming. However, remediation of Cr+6 by microbes is viable, efficient, and cost-effective. In this context, plant growth-promoting rhizobacteria Acinetobacter bouvetii P1 isolated from the industrial zone was tested for its role in relieving Cr+6 induced oxidative stress in sunflower. At the elevated Cr+6 levels and in the absence of P1, the growth of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…Both strains of bacteria used are positive producers of proline, under saline medium in vitro. The proline produce by Acinetobacter baumannii was 9.1 ppm and by Brevundimonas olei was 7.4 ppm, this agrees with Qadir et al, (2021), who studied that the Acinetobacter bouvetii P1 boosted sunflower by increasing the ________________________________________________ Egypt. J.…”
Section: Prolinsupporting
confidence: 83%
“…Both strains of bacteria used are positive producers of proline, under saline medium in vitro. The proline produce by Acinetobacter baumannii was 9.1 ppm and by Brevundimonas olei was 7.4 ppm, this agrees with Qadir et al, (2021), who studied that the Acinetobacter bouvetii P1 boosted sunflower by increasing the ________________________________________________ Egypt. J.…”
Section: Prolinsupporting
confidence: 83%
“…The use of microbes to help the crop plants in the HMs contaminated soils is considered to be more practical, easy, cost effective and safe to the ecosystem [4,9,25]. Exploration of beneficial microbes, such as endophytes (microbes live in symbiotic relations with host plants) and their application in HMs contaminated soils can lead to a sustainable agriculture and access to a safer food [4,16,40]. Qadir, et al [8] observed Cr remediation potential of endophytic Aspergillus niger in sunflower.…”
Section: Plos Onementioning
confidence: 99%
“…Certainly, Pb tolerance is only one of the factors involved in fungal behaviour. For instance, interactions between plants and their endophytic organisms can alter the concentration of phytoregulatory compounds and antioxidant responses (Qadir et al 2021(Qadir et al , 2022. These aspects can be relevant as the focus of future studies to determine if phytoremediation assisted by endophytic fungi in similar environments of cold steppe could become a viable strategy.…”
Section: Effect Of Pb On the Fungal Growthmentioning
confidence: 99%